Pilot project for a recovery‐oriented, DBT‐informed skill‐building education course for families of adults with borderline personality, bipolar or major depressive disorders. Issue 1 (13th October 2021) - Mannion, Edie; Lukens, Jonathan; Solomon, Phyllis; Lowery, MaryCatherine; Snitzer, Lisa
Abstract: There are a variety of educational interventions for families who have a relative with a mental health disorder. However, for those with one or more emotion dysregulation disorders, there are limited options. This article reports on the results of a pilot project using a quasi‐experimental design with a sample of 270 (intervention = 217, control = 53) to assess an intervention, Getting Off the Emotional Roller Coaster Skill ‐ Building Family Education Course (GOER Family Course), for families coping with and managing emotion regulation disorders in a loved one which are often misdiagnosed or co‐occurring. This intervention was effective in reducing caregiver burden [ F (1, 120) = 12.25, p  = 0.001], while improving attitudes, knowledge, and skills [ F (1, 170) = 6.16, p  = 0.014]. It fills an important gap in available resources for families faced with challenges and responsibilities that these disorders can present, especially when inaccurately diagnosed or receiving ineffective treatment. While there is a need for further research and adaptation to virtual learning, the preliminary results show positive effects. Resumen: Existen varias intervenciones educativas para las familias que tienen un familiar con un trastorno de salud mental. Sin embargo, para aquellos que padecen uno o más trastornos de desregulación emocional, existen pocas opciones. En este artículo se informan los resultados de un proyecto piloto usando un diseño cuasiexperimental con una muestra de 270 personas (intervención=217, de referencia=53) para evaluar una intervención llamada Bajarse de la montaña rusa emocional: curso de capacitación familiar para el desarrollo de habilidades (Curso familiar GOER, por sus siglas en inglés), orientado a familias que enfrentan y manejan trastornos de regulación emocional en un ser querido, los cuales generalmente están mal diagnosticados o son concomitantes. Esta intervención fue eficaz para reducir el agobio de los cuidadores [ F (1, 120 )=12.25, p=.001 ] y a la vez mejorar las actitudes, el conocimiento y las habilidades [ F (1, 170)=6.16, p=.014 ]. Además, llena un vacío importante en los recursos disponibles para las familias que enfrentan las dificultades y las responsabilidades que estos trastornos pueden presentar, especialmente cuando tienen un diagnóstico impreciso o reciben un tratamiento ineficaz. Si bien es necesario continuar investigando y adaptarse a la enseñanza virtual, los resultados preliminares indican efectos positivos. 摘要: 对于亲属患有精神健康障碍的家庭有各种教育干预措施。然而，对于那些有一种或多种情绪失调障碍的人来说，选择则是有限的。本文报告了一个试点项目的研究结果，使用的是一项针对需要应对和管理亲人情绪调节障碍的准实验设计(干预=217，对照=53)来评估GOER家庭课程的干预效果（即get Off the Emotional Roller Coaster技能建设家庭教育课程）。他们的亲人的精神障碍疾病经常被误诊或与物质滥用是同时发生的。这种干预措施可以有效地减轻护理人员的负担 [ F (1, 120 )=12.25, p=.001 ]，同时改善态度、知识和技能 [ F (1, 170)=6.16, p=.014 ]。面临这些精神疾病带来的挑战和责任的家庭，特别是在疾病诊断不准确或病人接受无效治疗时，有哪些可用资源，此研究填补了针对这个话题研究方面的空白。虽然虚拟学习还需要进一步地去研究和适应，但初步研究结果显示有积极的效果。